Structural performance of reinforced concrete double layer bamboo bubble slab under uniformly distributed load / Mohd Samsudin Abdul Hamid... [et al.] - Abdul Hamid, Mohd Samsudin; Zulkiple, Muhammad Zaim; Muhammad Azlan, Hafizah; Mohamad Sakdun, Noor Syafeekha (Universiti Teknologi MARA Cawangan Pulau Pinang, 2023)
The architectural use areas in the structure are formed by reinforced concrete (RC) slabs, which transport vertical loads to the beams, columns, load-bearing walls, and shear walls. The slab is an important structural member of reinforced concrete building structures and concrete-intensive parts of structural members. . The slab deflects significantly when the load acting on the slab or the clear span between columns is large. As a result, the slab's thickness increases to accommodate the load received. Since this slab's self-weight increases as the thickness increases, the slabs get heavier and causes the slab unable to withstand the load and to produce cracks on the surface. At the turn of the twentieth and twenty-first centuries, the creation of the bubble deck slab became an innovation to replace conventional slab. This study used bamboo as the bubble material in reinforced concrete bubble slab. This study examined and assessed the mechanical properties and structural behaviour of bamboo as a bubble in supported reinforced concrete double-layer bamboo bubble slab under a uniformly distributed load. In this research, 500 mm x 1250 mm x 175 mm supported reinforced concrete slabs C25 (1 sample) and C30 (1 sample) with double layer (DL) bamboo bubble slabs were constructed. Both samples were compared with the control sample (CS) for each slab type. It was found that the maximum displacement occurred at the centre of the slab, with 6.45 mm for DL25 and 6.89 mm for DL30. According to stress-strain analysis, the double layer bamboo slab produced a lower stress value than the control sample. Since the values were smaller than 2, DL25 and DL30 slab performed better for the ductility factor than CS25 and CS30. As a result, the displacement, ductility and section capacity were improved by employing bamboo as a bubble material in a reinforced concrete slab.